Integrating specialist palliative care to improve care and reduce suffering: cystic fibrosis (InSPIRe:CF) – study protocol for a multicentre randomised clinical trial. Issue 1 (20th September 2022) - Lowers, Jane; Dellon, Elisabeth P; Stephenson, Anne; Arnold, Robert; Althouse, Andrew; Jeong, Kwonho; Dubin, Ethan; Soodalter, Jesse; Hovater, Cade; Bakitas, Marie; Goggin, Jessica; Hunt, William; et al.
Abstract : Introduction: Cystic fibrosis (CF) is a life-limiting genetic disorder estimated to affect more than 160 000 individuals and their families worldwide. People living with CF commonly experience significant physical and emotional symptom burdens, disruptions to social roles and complex treatment decision making. While palliative care (PC) interventions have been shown to relieve many such burdens in other serious illnesses, no rigorous evidence exists for palliative care in CF. Thus, this study aims to compare the effect of specialist palliative care plus usual CF care vs usual CF care alone on patient quality of life. Methods and analysis: This is a five-site, two-arm, partially masked, randomised superiority clinical trial. 264 adults with CF will be randomly assigned to usual CF care or usual CF care plus a longitudinal palliative care intervention delivered by a palliative care specialist. The trial's primary outcome is patient quality of life (measured with the Functional Assessment of Chronic Illness Therapy-Palliative care instrument). Secondary outcomes include symptom burden, satisfaction with care and healthcare utilisation. Outcomes will be measured at 12 months (primary endpoint) and 15 months (secondary endpoint). In addition, we will conduct qualitative interviews with patient participants, caregivers, and palliative care and CF care team members to explore perceptions of the intervention's impact and barriers and facilitators to dissemination. Ethics and dissemination: Human subjects research ethics approval was obtained from all participating sites, and all study participants gave informed consent. We will publish the results of this trial in a peer-reviewed journal. Trial registration number: ISRCTN53323164 .